The Quality of Academic Supervision and its Role in Improving Scientific Research Outputs in Libyan Universities: An Analysis within the Framework of Academic Governance - Hani Hussein Khalifa Muftah; Dr. Awad Ahmed Mohamed Al-Ruwati (Journal of Scientific and Human Dimensions, 2026)
This study aims to examine the role of academic supervision quality in improving the output of scientific research in graduate programs at Libyan universities, given the growing need to enhance institutional competitiveness through improved research quality. The research problem stems from a practical and methodological gap in interpreting the relationship between supervision mechanisms and the quality of research outputs when subjected to the principles of academic governance, particularly in aspects related to statistical analysis, methodology, and scientific writing. Therefore, the study sought to analyze this relationship by employing the academic governance framework as a proposed explanatory framework. To achieve this objective, the study adopted a descriptive-analytical approach, collecting data using a questionnaire distributed to a simple random sample of 110 faculty members in accounting departments at Libyan universities, according to the Krejcie & Morgan (1970) table. The data were then subjected to statistical analysis using SPSS software, employing descriptive and inferential methods, including correlation coefficients and regression analysis. The study concluded with several key findings, most notably: * A relatively high level of academic supervision quality exists in Libyan universities. * A statistically significant positive impact of supervision quality on improving scientific research outputs, particularly in the areas of analysis and interpretation. * The pivotal role of academic governance principles in enhancing the efficiency of supervisory practices and improving the quality of research output is confirmed. The study concluded with a set of recommendations, the most important of which are: * Academic supervision practices should be governed by a unified and clearly defined academic governance framework. * Periodic scientific follow-up mechanisms should be activated to ensure that supervisory practices are consistent with international quality standards.